2004
DOI: 10.1300/j006v24n04_02
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' Perceptions of Their Children's Use of Powered Mobility

Abstract: Physical therapists and occupational therapists frequently assist parents with the exploration and use of powered wheelchairs for their children with physical disabilities. The purpose of this study was to explore parents' experiences and perceptions of their children's experiences with the receipt and use of powered mobility. Qualitative methods were used to gain insight into the experiences of five mothers of children with physical disabilities who use powered wheelchairs. Information was collected during in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
151
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(162 citation statements)
references
References 22 publications
5
151
0
4
Order By: Relevance
“…Despite the adoption of the ICF, the current culture of pediatric rehabilitation and caregivers alike view the use of powered mobility devices as a "last resort, " once all other efforts toward the skill of walking have been exhausted (Bottos and Gericke, 2003;Wiart et al, 2004;Rosen et al, 2009;Feldner et al, 2016). This represents a dichotomous view of thinking suggesting that self-directed mobility should be achieved by either a powered mobility device or walking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the adoption of the ICF, the current culture of pediatric rehabilitation and caregivers alike view the use of powered mobility devices as a "last resort, " once all other efforts toward the skill of walking have been exhausted (Bottos and Gericke, 2003;Wiart et al, 2004;Rosen et al, 2009;Feldner et al, 2016). This represents a dichotomous view of thinking suggesting that self-directed mobility should be achieved by either a powered mobility device or walking.…”
Section: Discussionmentioning
confidence: 99%
“…This represents a dichotomous view of thinking suggesting that self-directed mobility should be achieved by either a powered mobility device or walking. This dichotomous view may persist, in part, because researchers and caregivers have observed that the inability to walk is considered the most visible signifier of disability (Wiart et al, 2004;Daudji et al, 2011;Gibson and Teachman, 2012). For example, when comparing a walker device to a wheeled mobility device, a caregiver expresses Especially the kids at school, they think it's pretty neat that he's walking like they are.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One hundred and sixty nine users (31%) were provided with SS ( Recent recommendations emphasize the importance of motor and cognitive skills development and the ability to explore the environment as reasons for powered mobility being provided for very young children (aged 12-13 months onwards) [25][26][27] . In addition, early introduction of an EPIOC allows children and families to plan for future environmental adaptations and make proactive choices for housing and vehicles 27 .…”
Section: Equipmentmentioning
confidence: 99%
“…In addition, early introduction of an EPIOC allows children and families to plan for future environmental adaptations and make proactive choices for housing and vehicles 27 . Consequently these issues need further publicity throughout the UK.…”
Section: Equipmentmentioning
confidence: 99%